2011
DOI: 10.1007/s11703-010-1070-2
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate induction of antioxidant defense and glyoxalase system by exogenous proline and glycinebetaine is correlated with salt tolerance in mung bean

Abstract: The purpose of this study was to assess the synergistic effects of exogenously applied proline and glycinebetaine (betaine) in antioxidant defense and methylglyoxal (MG) detoxification system in mung bean seedlings subjected to salt stress (200 mmol$L -1 NaCl, 48 h). Seven-day-old mung bean seedlings were exposed to salt stress after pre-treatment with proline or betaine. Salt stress caused a sharp increase in reduced glutathione (GSH) and oxidized glutathione (GSSG) content in leaves, while the GSH/GSSG ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 87 publications
4
48
1
2
Order By: Relevance
“…Moreover, proline plays vital role in wide range of protective responses including osmotic adjustment, stabilizer for cellular structure and reducing damage to photosynthetic apparatus (Nounjan et al, 2012). Hossain et al (2011) demonstrated that exogenous proline provided a protective action against abiotic stress-induced oxidative damage by reducing H2O2 and lipid peroxidation level and by enhancing antioxidant defense and methylglyoxal detoxification systems. In addition to this, exogenous proline also prevents protein aggregation and stabilization of M4 lactate dehydrogenase during extreme temperatures, protection of nitrate reductase during heavy metal and osmotic stress (Szabados and Savouré, 2010).…”
Section: Proline Content In Leavesmentioning
confidence: 99%
“…Moreover, proline plays vital role in wide range of protective responses including osmotic adjustment, stabilizer for cellular structure and reducing damage to photosynthetic apparatus (Nounjan et al, 2012). Hossain et al (2011) demonstrated that exogenous proline provided a protective action against abiotic stress-induced oxidative damage by reducing H2O2 and lipid peroxidation level and by enhancing antioxidant defense and methylglyoxal detoxification systems. In addition to this, exogenous proline also prevents protein aggregation and stabilization of M4 lactate dehydrogenase during extreme temperatures, protection of nitrate reductase during heavy metal and osmotic stress (Szabados and Savouré, 2010).…”
Section: Proline Content In Leavesmentioning
confidence: 99%
“…Excess Na + in root cells competes with K + for uptake causing ionic imbalance (Bavei et al, 2011). Uptake of K + is reduced due to having similar physiochemical properties of Na + under high salinity (Hossain et al, 2011). Salt stress induces disturbance in various metabolic processes such as photosynthesis, stomatal regulation and protein synthesis (Nusrat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…GSH, a non-enzymatic antioxidant, is a low-molecular-weight thiol involved in various metabolic processes that acts as an important plant defense molecule against environmental stresses, including trace elements (Hossain et al, 2011). It is one of the major antioxidant and redox buffers in plants, abundantly found in all cell compartments.…”
Section: Introductionmentioning
confidence: 99%